Cretaceous entomopathogenic fungi illuminate the early evolution of insect-fungal associations - Zhuang, Yuhui; Luo, Cihang; Tang, Dexiang; Araújo, João Paulo Machado de; Yu, Hong; Zhao, Jing; Haelewaters, Danny; Nyunt, Thet Tin; Zhang, Qingqing; Jarzembowski, Edmund A; Meng, Guoliang; Ran, Hao; et al. (Proceedings. Biological sciences, 2025)
Throughout evolution, entomopathogenic (insect-pathogenic) fungi have played a pivotal role in regulating insect populations. However, little is known about ancient entomopathogenic fungi due to the scarcity of fossils displaying typical pathogenic structures on their presumed hosts. Here, we report two new fungi, Paleoophiocordyceps gerontoformicae sp. nov. and Paleoophiocordyceps ironomyiae sp. nov., from mid-Cretaceous Kachin amber (approx. 99 million years old). They share common traits with Ophiocordyceps and are associated with an ant pupa and a fly, respectively. These fossils are among the oldest fossil records of animal-pathogenic fungi. In addition, we performed a divergence time estimation analysis showing that Ophiocordyceps likely originated during the Early Cretaceous. We further compiled the hosts of extant Ophiocordyceps and inferred the evolution of host associations within the genus based on ancestral character state reconstruction. Our results suggest that Ophiocordyceps made a host jump from Coleoptera to Lepidoptera and Hymenoptera during the Cretaceous, and its subsequent speciation was probably related to the increase in diversity and abundance of its moth and ant hosts. Our results not only highlight the ecological significance of pathogenic fungi in Mesozoic terrestrial ecosystems, but also provide new insights into the coevolution between entomopathogenic fungi and host insects.
Keywords: ant; Insecta; biologická evoluce; zkameněliny; jantar; Hypocreales; Amber; hmyz; Biological Evolution; fossil; Fossils; amber; zvířata; Mesozoic; fylogeneze; Diptera; Phylogeny; host–parasite association; Animals